Diagnosing MALT Gastric Lymphoma in Gastroenterologist’s Practice, a Clinical Observation - E. Ya. Selezneva; N. A. Shcherbakova; Yu. V. Embutnieks; E. V. Bystrovskaya; S. G. Khomeriki (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2021)
Aim. A clinical case description to highlight challenges in diagnosing MALT lymphoma presented in infiltrative ulcer-ative lesions.Key points. A 60-yo patient was admitted to the Loginov Moscow Clinical Scientific Centre with epigastric pain and an 18 kg weight loss over past 4 months. A history of repeated outpatient endoscopic examinations revealing subse-quently ulcerative and infiltrative ulcerative gastric lesions of unestablished origin. A complex examination combin-ing oesophagogastroduodenoscopy (OGDS), endosonography (EUS), multislice computed tomography (MSCT), morphological and immunohistochemical (IHC) assays elicited the MALT gastric lymphoma IIE stage involving para-gastric and intraperitoneal lymph nodes. The first treatment stage included line-1 eradication therapy, rabeprazole 20 mg x 2 times a day, amoxicillin 1000 mg x 2 times a day, clarithromycin 500 mg x 2 times a day, bismuth tripotas-sium dicitrate 240 mg x 2 times a day — for 14 days. Accounting for the process prevalence and stage, six courses of R-CHOP polychemotherapy (PCT) were ordered by haematologist.Conclusion. This observation demonstrates a targeted-biopsy endoscopic examination followed by morphological, IHC, EUS (for invasion depth) and MSCT (for process advancement) assays to be decisive in differential diagnosis of ulcerative and infiltrative ulcerative gastric lesions.